Social Exchanges and P2P accommodation: Residents’ Perceptions in a Neighbourhood Context - Stergiou, Dimitrios P.; Farmaki, Anna; Efthymiadou, Fani (My University, 2022)
The rapid growth of peer-to-peer (P2P) accommodation has challenged the sustainability efforts of destinations, due to the numerous negative impacts accrued from the influx of tourists in residential areas. Even so, scant attention has been paid to the perceptions of local residents with regard to associated impacts. This chapter aims to examine the perceptions of the residents of Koukaki (Athens, Greece) regarding the impacts of Airbnb at the neighbourhood level, using social exchange theory. Findings reveal a dominance of negative perceptions of socio-economic and environmental impacts and identify attempts from residents to mitigate associated impacts. Drawing from the literature and empirical findings, the chapter offers a framework which acknowledges the mediating role of platforms and property owners in the social exchanges between residents and guests. The chapter concludes with a discussion of implications, contributing towards the adoption of an anthropocentric and inclusive approach on P2P accommodation.
Keywords: Airbnb; P2P accommodation; Neighbourhoods; Impacts; Social exchange theory